Diseño de un modelo de tratamiento de Contaminantes Orgánicos por el efecto Foto Fenton en muestras de Aguas de Zonas de descarga del Río Cutuchi, Provincia de Cotopaxi periodo 2019-2020. - Romero Castillo, Génesis Marbely. (2020)
The shortage of quality water is a worldwide problem that is increasing due to the pollution. For this reason, the treatment and reuse of polluted water in becoming necessary. The emission of contaminants of emerging concern (CECs) is of great importance and many organizations are trying to found solutions for this problem. CECs are mostly organic micro pollutant agents that are not regulated by law and, nowadays, are the main target of the legislation because of their important environmental impact. The Advanced Oxidation Processes (AOPs) are the necessary methods for their elimination. They present a high capacity to generate reactive oxygen species, such as hydroxyl radicals, and achieve the total or partial decomposition of components that are very resistant to the conventional methods (Waste Water Treatment Station, WWTS). The Photo-Fenton treatment, in optimal pH conditions, has been demonstrated to be Capable of eliminating these pollutants of the sewage. This treatment generates an effluent that is non-toxic for the activated sludge; therefore, it is possible to complement the treatment with a biological purifying system. Moreover, economic saving has been proved and also an environmental benefit, if the polluted water goes through convenient treatment before pouring it in the WWTS.